B6. Выделение квадрата двучлена. Извлечение квадратного корня (ЕГЭ-2009, ЕГЭ-2010)
В6. Найдите значение выражения x - 2√x - 1 + √x + 2√x - 1 при х = 1,2007.

1) √x - 2√x - 1 = √1 - 2√x - 1 + (х - 1) = √(1 - √x - 1)2 = |1 - √x - 1| = 1 - √x - 1,
т.к. 1 - √x - 1 = 1 - √1,2007 - 1 = 1 - √0,2007 > 0.

2) √x + 2√x - 1 = √1 + 2√x - 1 + (х - 1) = √(1 + √x - 1)2 = |1 + √x - 1| = 1 + √x - 1.
3) √x - 2√x - 1 + √x + 2√x - 1 = (1 - √x - 1) + (1 + (√x - 1) = 2.
Ответ: 2

Deprecated: Function set_magic_quotes_runtime() is deprecated in /home/muzeinie/ege-trener.ru/5de8950cf9bdb5a2f0c69d692e18c77c/sape.php on line 221

Deprecated: Function set_magic_quotes_runtime() is deprecated in /home/muzeinie/ege-trener.ru/5de8950cf9bdb5a2f0c69d692e18c77c/sape.php on line 227